Transformasi Profesional Guru Pendidikan Anak Usia Dini melalui Participatory Action Research dalam Pembelajaran Saintifik - Librianty, Herwina Dewi; Yennizar, Yennizar; Zukhairina, Zukhairina (Universitas Nurul Jadid, 2026)
This community service program addressed the limited implementation of inquiry-based science learning in early childhood education centers in Batanghari Regency, where classroom practice was still largely dominated by teacher demonstrations and worksheets. The program aimed to strengthen teachers’ professional capacity to design and implement developmentally appropriate scientific learning. Participants included 120 teachers from 20 kindergartens across Muara Bulian, Bajubang, and Pemayung districts. The program was implemented over six months using Participatory Action Research (PAR) through three cycles of collaborative planning, classroom action, observation, and reflection. Data were collected through classroom observation, teachers’ reflective journals, classroom documentation, and a scientific learning implementation rubric. The findings showed measurable improvements in classroom practice: the use of open-ended questions rose from 22% to 68%, facilitation of direct experimentation from 15% to 73%, constructive responses to children’s inquiry from 12% to 75%, documentation of children’s exploration from 10% to 64%, and participation in reflective peer discussion from 8% to 82%. Moreover, all 20 participating institutions developed local resource-based science corners, and the teacher learning community continued to function through the end of the program. The program demonstrates that theory-guided and contextually grounded PAR can effectively strengthen scientific learning practices and support the professional identity of early childhood teachers.